Uji Diagnostik Squatting Stress Echocardiography dengan Angiografi Koroner dalam Mendiagnosis Penyakit Jantung Koroner - Andy Rahman; Mefri Yanni; Masrul Syafri (Jurnal Kardiologi Indonesia, 2016)
Background: In patients with significant coronary heart disease (CHD), increased preload and afterload during a squat can cause wall motion abnormalities (WMA) which can be detected on echocardiography. This study was conducted to determine the diagnostic value of stress echocardiography squatting as a non-invasive examination of a relatively simple, inexpensive, and safe in the detection of coronary artery stenosis in stable CHD and unstable angina patients.Methods: This study was a cross-sectional design. The subjects were all patients with stable CHD and unstable angina whom were treated in Instalasi Pusat Jantung Rumah Sakit Dr. M. Djamil Padang from May to July 2016. Subjects underwent squatting stress echocardiography procedures followed by coronary angiography. Diagnostic test was used to determine the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of squatting stress echocardiography.Results: The sensitivity, specificity, and accuracy of squatting echocardiography for diagnosis of CAD were 90.3%, 88.9% and 89.7%, respectively.Conclusion: Squatting stress echocardiography can be proposed as a non-invasive examination which is relatively simple, inexpensive and safe to detect coronary artery stenosis on patients with stable CHD and unstable CHD.